Public attention to extreme weather as reflected by social media activity. (3rd May 2019) - Silver, Amber; Andrey, Jean
Abstract: Recent advancements in the development of information and communication technologies have revolutionized risk and crisis communication. This research explored how social media facilitates information seeking, interpretation, and dissemination during extreme weather. Using Twitter data collected during a tornado‐warned storm, this study explored the activity of different actor groups. The findings demonstrate that weather professionals and weather enthusiasts acted as "key stewards" who facilitated discussion during the event. Citizens engaged in the dialogue predominately by retweeting and by sharing personal observations of the storm. The results highlight the usefulness of Twitter for the propagation of both official and unofficial storm‐related information. This study also supports previous research that suggests that tweet activity may be a reliable indicator of public attention.